Characteristics and Predictors of Late Right Heart Failure After Left Ventricular Assist Device Implantation. Issue 3 (2nd October 2022) - Alkhunaizi, Fatimah A.; Azih, Nnamdi I.; Read, Jacob M.; Goldberg, Rachel L.; Gulati, Arune A.; Scheel, Paul J.; Muslem, Rahatullah; Gilotra, Nisha A.; Sharma, Kavita; Kilic, Ahmet; Houston, Brian A.; Tedford, Ryan J.; et al.
Abstract : Late right heart failure (LRHF) following left ventricular assist device (LVAD) implantation remains poorly characterized and challenging to predict. We performed a multicenter retrospective study of LRHF in 237 consecutive adult LVAD patients, in which LRHF was defined according to the 2020 Mechanical Circulatory Support Academic Research Consortium guidelines. Clinical and hemodynamic variables were assessed pre- and post-implant. Competing-risk regression and Kaplan–Meier survival analysis were used to assess outcomes. LRHF prediction was assessed using multivariable logistic and Cox proportional hazards regression. Among 237 LVAD patients, 45 (19%) developed LRHF at a median of 133 days post-LVAD. LRHF patients had more frequent heart failure hospitalizations ( p < 0.001) alongside other complications. LRHF patients did not experience reduced bridge-to-transplant rates but did suffer increased mortality (hazard ratio 1.95, 95% confidence interval [CI] 1.11–3.42; p = 0.02). Hemodynamically, LRHF patients demonstrated higher right atrial pressure, mean pulmonary arterial pressure, and pulmonary vascular resistance (PVR), but no difference in pulmonary arterial wedge pressure. History of early right heart failure, blood urea nitrogen (BUN) > 35 mg/dl at 1 month post-LVAD, and diuretic requirements at 1 month post-LVAD were each significant, independent predictors of LRHF in multivariable analysis. An LRHF prediction risk score incorporating these variables predicted LRHF with excellent discrimination (log-rank p < 0.0001). Overall, LRHF post-LVAD is more common than generally appreciated, with significant morbidity and mortality. Elevated PVR and precapillary pulmonary pressures may play a role. A risk score using early right heart failure, elevated BUN, and diuretic requirements 1 month post implant predicted the development of LRHF. Abstract :